HISTORY OF THE ORIGIN AND DEVELOPMENT OF SHAKHRISABZ (Conferencea, 2022)
The article describes the history of the city of Shakhrisabz and its development. Shahrisabz is one of the ancient cities. Shahrisabz is visited by many tourists from different cities.